A Case of Acute Massive Bioprosthetic Mitral Valve Thrombosis Leading to Fulminant Heart Failure. (11th January 2020) - Nesheiwat, Zeid; Shastri, Pinang; Vyas, Rohit; Burmeister, Cameron; Grande, Robert; Malas, Hazem
Abstract : Bioprosthetic valve thrombosis has been considered to be extremely unlikely, typically freeing patients from the potential complications of long-term anticoagulation. However, there have been several documented cases of bioprosthetic valve thrombosis and there are concerns that its incidence may be underreported. Experience with diagnosis and management of this condition is limited. Here, we present a case of acute massive bioprosthetic mitral thrombosis manifesting as fulminant heart failure.